The Prospect of Hydrolyzed Feather Meal as Ruminant Feeds Through Protein Quality Improvement by Microbes - Prayitno, CH; Suwandyastuti, SNO; Hidayat, Nur (ANIMAL PRODUCTION, 2003)
The waste of the broiler processing (feather) is a potential source for animal feed. However the presence of keratins cause limited of feather use. Before using, therefore, feather must be treated to hydrolyze cysteine disulfide bound dominating keratins protein. Enzymatic (biological) treatment using microbes will produce specific feather hydrolyzed and does not have negative impact on environment. The research objected to get the microbes which degradated selected keratins, improve protein quality of feather meal and find out the best ration formulation true in vitro the basic information to formulate in vivo ration. The research has been done in Laboratory of Animal Feedstuff Faculty of Animal Science UNSOED for eight months. Fermentation trial was done on liquid media with bath system. In vitro trial used of Tilley and Terry methods with parameter observe was dry matter digestibility, organic matter digestibility, protein degradation, total VFA and solubility in pepsin. Based on all parameter, on fermentation trial with Bacillus licheniformis decides broiler chicken feather had good prospect to be developed on feed protein source. In vitro trial recommended ration with formulation of fermented feather meal concentrate (15 percent), soybeans meal (5 percent), rice bran (20 percent), molasses (4 percent), mineral mix (1 percent), with forage: concentrate ratio 40 : 60 could be used as in vivo ration. (Animal Production 5(1): 19-24 (2003)Â Key words : Hydrolyze, Feather, Keratin, Digestibility, Ruminant